Comparison of Treatment Regimens in Management of Severe Hypercalcemia Due to Vitamin D Intoxication in Children - BEREKET, ABDULLAH (GALENOS YAYINCILIK, 2019)
Objective: No large study has been conducted to date to compare the effectiveness of prednisolone, alendronate and pamidronate as first-line treatment in children with hypercalcemia due to vitamin D intoxication. The aim was to perform a multicenter, retrospective study assessing clinical characteristics and treatment results. Methods: A standard questionnaire was uploaded to an online national database system to collect data on children with hypercalcemia (serum calcium level > 10.5 mg/dL) due to vitamin D intoxication [serum 25-hydroxyvitamin D (25(OH)D) level > 150 ng/mL] who were treated in pediatric endocrinology clinics. Results: Seventy-four children [median (range) age 1.06 (0.65-1.60) years, 45 males (61 %) from II centers] were included. High-dose vitamin D intake was evident in 77% of the cases. At diagnosis, serum calcium, phosphorus, alkaline phosphatase, 25(OH)D and parathyroid hormone concentrations were 15 +/- 3.2 mg/dl., 5.2 +/- 1.2 mg/dL, 268 +/- 132 IU/L, 322 (236-454) ng/ml, and 5.5 (3-10.5) pg/mL, respectively. Calcium levels showed moderate correlation with 25(OH)D levels (r(s) = 0.402, p <0.001). Patients were designated into five groups according to the initial specific treatment regimens (hydration-only, prednisolone, alendronate, pamidronate, and combination). Need for another type of specific drug treatment was higher in children who initially received prednisolone (p <0.000). Recurrence rate of hypercalcemia was significantly lower in children who were treated with pamidronate (p=0.02). Conclusion: Prednisolone is less effective in the treatment of children with severe hypercalcaemia secondary to vitamin D intoxication and timely implementation of other treatment regimens should be considered.
Keywords: Nutrition; rickets; stoss therapy; steroid; over-the-counter drugs; D DEFICIENCY; THERAPY; PAMIDRONATE; ALENDRONATE; RISK; PREVENTION; TOXICITY; INFANTS